Review on Joule-Thompson Effect Throttle Cryocooler - She Hailong; Cui Xiaoyu; Geng Hui; Pan Xiaoshan (Zhileng xuebao)
The recent development of micro-sized Joule–Thomson (J-T) effect throttle cryocoolers is reviewed in this paper. The existing technology and research results are summarized from the theoretical research and structural evolution of the cryocooler. Based on the analysis of relevant studies, the development direction of the micro-sized J-T effect throttle cryocooler is further prospected. With the expansion of application fields and advances in processing technology, the structure of cryocoolers is becoming increasingly compact and diversified. Multi-stage, multi-layer, multi-channel, micro-sized J-T effect throttle cryocoolers fabricated by micro-etching technology have much room for development. In terms of theoretical research, the current theoretical models are mostly based on different assumptions and simplification because of the complicated operation mechanism of the micro-sized J-T throttle cryocooler. Therefore, for future theoretical research of J-T effect throttle cryocoolers, it is necessary to establish and solve more practical theoretical models, and basic research results need to be considered and applied in a timely manner.